Safety of Ustekinumab in Inflammatory Bowel Disease: Pooled Safety Analysis of Results from Phase 2/3 Studies. Issue 7 (15th July 2021) - Sandborn, William J; Feagan, Brian G; Danese, Silvio; O'Brien, Christopher D; Ott, Elyssa; Marano, Colleen; Baker, Thomas; Zhou, Yiying; Volger, Sheri; Tikhonov, Ilia; Gasink, Christopher; Sands, Bruce E; et al.
Abstract: Background: Ustekinumab is currently approved globally in Crohn's disease (CD) and psoriatic diseases. Recent phase 3 data demonstrate safety/efficacy in ulcerative colitis (UC). Crohn's disease and UC phase 3 programs had similar study designs, facilitating integrated safety analyses. Methods: Data from 6 ustekinumab phase 2/3 CD and UC studies were pooled, and safety was evaluated through 1 year. Patients received 1 placebo or ustekinumab (generally 130 mg or ~6 mg/kg) intravenous induction, then subcutaneous (90 mg) maintenance every 8/12 weeks. Analyses incorporated all patients who received ≥1 ustekinumab dose. Safety outcomes are presented as percentages of patients (induction) and as number of patients with events per 100 patient-years of follow-up (through 1 year). For key safety events, 95% confidence intervals (CIs) are provided, as appropriate. Hazard ratios with 95% CIs from time-to-event analyses for serious adverse events and serious infections were also performed. Results: Through 1 year, 2574 patients received ustekinumab (1733 patient-years of follow-up). The number of patients with adverse events per 100 patient-years (placebo 165.99 [95% CI, 155.81–176.67] vs ustekinumab 118.32 [95% CI, 113.25–123.55]), serious AEs (27.50 [95% CI, 23.45–32.04] vs 21.23 [95% CI, 19.12–23.51]), infections (80.31 [95% CI, 73.28–87.84] vs 64.32 [95% CI, 60.60–68.21]), serious infections (5.53 [95% CI, 3.81–7.77] vs 5.02 [95% CI, 4.02–6.19]), and malignancies excluding nonmelanoma skin cancer (0.17 [95% CI, 0.00–0.93] vs 0.40 [95% CI, 0.16–0.83]) were similar between placebo and ustekinumab. Conclusions: The safety profile of ustekinumab across the pooled inflammatory bowel disease population through 1 year was favorable and generally comparable to placebo. These data are consistent with the established safety profile of ustekinumab across indications. ClinicalTrials.gov numbers: NCT00265122; NCT00771667; NCT01369329; NCT01369342; NCT01369355; NCT02407236.